Ensuring food and nutrition security in a green economy - Fan, Shenggen; Ringler, Claudia; Nkonya, Ephraim M.; Stein, Alexander J. (International Food Policy Research Institute, 2012)
As the population continues to grow and natural resources become scarcer, the need to shift toward an environmen-tally responsible, socially accountable, more equitable, and “greener” economy has become increasingly apparent. Despite differing perspectives and definitions among stakeholders, the “green economy” is often seen as an economy that pursues growth while also promoting sustainable development through more efficient use of resources. Thus aligned with concepts of sustainability, the objective of a green economy is to simultaneously work toward economic development, environmental protection, and greater social welfare, in particular by reducing reliance on fossil fuels and nonrenewable resources.